The Development of Zakat, Infaq, Sadaqah in Egypt: A Literature Review Approach - Mariam Elbanna (Walidem Institute and Publishing (WIP), 2024)
Objective: This study examines the development of Zakat, Infaq, and Sadaqah (ZIS) systems in Egypt through a comprehensive literature review, focusing on historical, legal, and social perspectives. The research aims to explore the evolution of these Islamic financial tools, which have long served as mechanisms for wealth redistribution and social welfare within the Islamic economy. In the face of rising poverty, unemployment, and other socioeconomic challenges in modern Egypt, this study investigates how traditional ZIS practices can be adapted to contemporary needs. Theoretical framework: The theoretical framework is based on the principles of Islamic economics, particularly those addressing wealth redistribution, social justice, and poverty alleviation. Literature Review: The literature review draws on previous studies and reports to analyze changes in ZIS implementation, considering evolving legal frameworks, shifting social expectations, and dynamic economic conditions. By bridging the gap between historical practices and modern demands, the study highlights the critical role of ZIS in addressing poverty and inequality in Egypt. Methods: This qualitative research employs a systematic review method, synthesizing data from academic publications, government reports, and non-governmental studies to identify trends, challenges, and opportunities in the ZIS systems. Results: The findings reveal that while progress has been made in the institutionalization and modernization of ZIS in Egypt, significant challenges remain. Key issues include inefficiencies in collection and distribution mechanisms, lack of public trust, and insufficient legal and regulatory frameworks. These factors limit the effectiveness of ZIS in reaching vulnerable populations and maximizing their potential impact. The study concludes that further reforms are essential to enhance the role of ZIS in Egypt's socioeconomic development. Specifically, improvements in transparency, accountability, and integration with modern financial systems are necessary to align ZIS practices with contemporary realities. Implications: The findings have implications for policymakers, Islamic scholars, and financial institutions, emphasizing the need to create a sustainable and equitable framework for ZIS that addresses pressing issues such as poverty and inequality. Novelty: This research offers a novel contribution by integrating historical, legal, and social perspectives into the analysis of ZIS systems in Egypt, providing a comprehensive understanding of their development and contemporary challenges. It underscores the importance of adapting Islamic financial practices to meet modern demands, paving the way for future research on optimizing ZIS for social justice and economic growth in diverse contexts.